Implementation of Eco-Innovation, Eco-Commitment, Eco-Opportunity in the Islamic Boarding School Environment: A Phenomenological Study on the Raudhatul Madinah Entrepreneur Islamic Boarding School - Syarifah HN., Lailatus; Amalia Rahman AJR; Nihayatu Aslamatis Solekah; Sandiani Sri Wahyuni (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
A phenomenon that is increasingly prevalent in Indonesia is the increasingly high unemployment rate. This is partly due to the low absorption rate for school freshgraduates who are not equipped with entrepreneurial skills, so this study seeks to explain the Eco-preneur system applied to the Raudhatul Madinah Entrepreneur Islamic boarding school educational institution as a form of cultivating the entrepreneurial character of students. This study uses a qualitative method through a phenomenological approach. In this approach, the researcher uses experienced and knowledgeable resource persons, namely the founder, caregivers, and students of the Raudhatul Madinah Islamic Boarding School. The results of the study explain that the Ecopreneur system applied in the pesantren environment is manifested in 3 (three) forms, including: (1) Eco-Innovation through the integrated organic farm system including land conversion, making organic probiotics etc., and radical innovation which includes innovation of pesantren organic satay products; (2) Eco-Commitment through the commitment of the pesnatren to maintain, protect, and not use synthetic materials; and (3) Eco-Opportunity which is reflected through the introduction of pesantren organic products.